Effect of Foliar Silicon Application on the Growth and Yield of Datu F1 Sweet Corn (Zea mays var. saccharata) - Corpuz, Jeremy (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study evaluated the effect of foliar silicon application on the growth and yield performance of Datu F1 sweet corn under local field conditions. It aimed to determine the influence of varying silicon rates on growth parameters, reproductive traits, and yield. The study was anchored on the concept that silicon enhances plant performance through physiological, structural, and biochemical mechanisms. A Randomized Complete Block Design (RCBD) was employed with four treatments and four replications, involving different rates of foliar silicon applied at three growth stages. Data were collected using standard field measurements, including plant height, leaf area, number of days to silking, ear length, ear diameter, and yield per hectare, and were analyzed using Analysis of Variance (ANOVA). Results showed that foliar silicon application significantly improved leaf area, plant height, ear length, ear diameter, and yield, while also promoting earlier silking compared to the control. Silicon-treated plants consistently outperformed untreated plants across all parameters, although differences among silicon rates were minimal. The findings confirm that silicon enhances growth performance and crop productivity of sweet corn under the given conditions. The study concludes that foliar silicon application is an effective strategy for improving sweet corn production, with moderate application rates recommended for optimal results and cost efficiency. This study supports SDG 2 (Zero Hunger) by contributing to increased agricultural productivity and food security, and SDG 8 (Decent Work and Economic Growth) by improving the income potential of farmers. The findings contribute to agricultural and socio-economic sustainability by promoting efficient crop management practices that enhance productivity while supporting resource-efficient and resilient farming systems.